2015
DOI: 10.1007/s00401-015-1435-y
|View full text |Cite
|
Sign up to set email alerts
|

Beta-amyloid deposition in chronic traumatic encephalopathy

Abstract: Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease associated with repetitive mild traumatic brain injury. It is defined pathologically by the abnormal accumulation of tau in a unique pattern that is distinct from other tauopathies, including Alzheimer’s disease (AD). Although trauma has been suggested to increase amyloid β peptide (Aβ) levels, the extent of Aβ deposition in CTE has not been thoroughly characterized. We studied a heterogeneous cohort of deceased athletes and military veteran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
237
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 246 publications
(249 citation statements)
references
References 54 publications
9
237
3
Order By: Relevance
“…CTE is primarily known as a tauopathy; however, because 52% of 114 neuropathologically confirmed CTE brains also demonstrate concomitant Ab plaque deposition, 11 we wanted to introduce a mouse model that has the ability to produce both amyloid and tau pathology. The 3xTg-AD mouse overexpresses mutant human APP and tau, leading to amyloid plaques and tau tangles in the brain.…”
Section: Rmtbi Does Not Induce Amyloid or Tau Pathology In 3xtg-ad Micementioning
confidence: 99%
See 2 more Smart Citations
“…CTE is primarily known as a tauopathy; however, because 52% of 114 neuropathologically confirmed CTE brains also demonstrate concomitant Ab plaque deposition, 11 we wanted to introduce a mouse model that has the ability to produce both amyloid and tau pathology. The 3xTg-AD mouse overexpresses mutant human APP and tau, leading to amyloid plaques and tau tangles in the brain.…”
Section: Rmtbi Does Not Induce Amyloid or Tau Pathology In 3xtg-ad Micementioning
confidence: 99%
“…9,10 This disease is associated primarily with the buildup of neurofibrillary tangles of hyperphosphorylated tau throughout the brain; however, 52% of cases also present with diffuse amyloid-b (Ab) deposits. 11 There has been difficulty reproducing tau pathology in rodents after rmTBI, and to date the only study that has seen a chronic (21 days after TBI) increase in hyperphosphorylated tau after rmTBI has required the use of aged tau transgenic mice to observe an effect. 12 In this study, we examine changes to the neuronal structure and brain pathology after a single mTBI or rmTBI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They also controls genes regulating cell changes, including cell proliferation, survival and oxidative defense (23). It has been indicated that the decrease of FoxOs in hematopoietic stem cells may cause a decrease in antioxidase including reactive oxygen species, manganese superoxide dismutase and scavenger enzymes, resulting in dysfunction of mitochondria and cell apoptosis (24).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Patients with AD can have memory loss, mood swings, and agitation, just as patients with CTE can have those same symptoms. CTE is defined pathologically by the abnormal accumulation of the tau protein in a pattern that is different from other tauopathies, such as AD and FTD.…”
mentioning
confidence: 99%